Business Plan for Hera Virtual Assistant Agency - Yusubova, Jala (ADA University, 2022)
Nowadays, the world is rapidly digitalizing reshaping every aspect of human living from social life to work environment. The digitalization of workplaces occurs through more and more employers switching to telework in their operations or outsourcing some of their business activities to virtual assistants who produce the same job for cheaper (VAs). Even though the VA industry is globally expanding, there is no such business in Azerbaijan so far which is both a gap and opportunity in the market that inspired me to create the given business plan. Limited in both financial and physical resources, micro and small businesses are evaluated as potential customers of the given business. The online survey conducted among over 200 micro and small Azerbaijani business owners showed that 70% of them are ready to outsource some of their business activities to VAs, namely graphics/ web design, social media management, content writing and administrative tasks which ultimately became the first four services we aim to offer to our potential clients in 2023-2026. Our calculations showed that to start the business and to be able to operate it without profit during the first quarter of 2023, we will need 45.000 AZN which we aim to fund with a bank loan. Overall, the financial analysis of the company showed that it is a profitable investment option since the business is expected to cover its costs starting from the second quarter of 2023 and make considerable net profit each year being almost 460.000 AZN in 2026 with return on investment of over 10%.
Keywords: Telework.; Virtual assistant.; Return on investment.; Business